pointblue/ContinentalWESEestimates: ContinentalWESEestimates - Leo Salas (Zenodo, 2021)
This repository contains the R markdown notebooks, R scripts, and all datasets used in developing the analyses and results presented in the manuscript: "Insights from the first global population estimate of Weddell seals in Antarctica", published in Scicen Advances (2021) by Michelle LaRue1, Leo Salas, Nadav Nur, David Ainley, Sharon Stammerjohn, Jean Pennycook, Melissa Dozier, Jon Saints, Kostas Stamatiou, Luke Barrington,and Jay Rotella.